2005
DOI: 10.1074/jbc.m411334200
|View full text |Cite
|
Sign up to set email alerts
|

Structure of the Dimeric PufX-containing Core Complex of Rhodobacter blasticus by in Situ Atomic Force Microscopy

Abstract: We have studied photosynthetic membranes of wild type Rhodobacter blasticus, a closely related strain to the well studied Rhodobacter sphaeroides, using atomic force microscopy. High-resolution atomic force microscopy topographs of both cytoplasmic and periplasmic surfaces of LH2 and RC-LH1-PufX (RC, reaction center) complexes were acquired in situ. The LH2 is a nonameric ring inserted into the membrane with the 9-fold axis perpendicular to the plane. The core complex is an S-shaped dimer composed of two RCs, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

6
129
1

Year Published

2007
2007
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 123 publications
(136 citation statements)
references
References 44 publications
6
129
1
Order By: Relevance
“…The N-terminal part of PufX was found to be critical for the formation of dimers of the RC-LH1 and, in the refined dimer model, the N-termini of the two PufX proteins point to the interface between the monomers. In a second type of model, PufX is placed at the dimerization interface in the centre of the dimer complex and is itself also thought to be dimerized [5,10,12]. In another model, the two PufX molecules are also placed in the centre of the dimer, but not in close contact [8].…”
Section: Introductionmentioning
confidence: 99%
“…The N-terminal part of PufX was found to be critical for the formation of dimers of the RC-LH1 and, in the refined dimer model, the N-termini of the two PufX proteins point to the interface between the monomers. In a second type of model, PufX is placed at the dimerization interface in the centre of the dimer complex and is itself also thought to be dimerized [5,10,12]. In another model, the two PufX molecules are also placed in the centre of the dimer, but not in close contact [8].…”
Section: Introductionmentioning
confidence: 99%
“…We have demonstrated that the comparatively disordered intracytoplasmic membrane from the model photosynthetic bacterium Rhodobacter sphaeroides can be successfully imaged by AFM (9) to reveal the hidden architecture that nature has developed to harvest, transfer, and finally utilize light energy with great efficiency. Scheuring and co-workers have also produced high resolution images of the photosynthetic membranes of Blastochloris viridis (10), Rhodospirillum photometricum (11), Rhodobacter blasticus (12), and Phaeospirillum molischianum (13), allowing a comparison of the differing strategies that purple bacteria have evolved for the harvesting and utilization of light energy (14).…”
mentioning
confidence: 99%
“…Because of the lack of a high-resolution x-ray structure, most proposed geometries are based on low-resolution electron microscopy/atomic force microscopy data (24)(25)(26)(27)(28). A detailed discussion on this issue can be found in ref.…”
mentioning
confidence: 99%